
If \[f\left( x \right)=\dfrac{2018x-2019}{x+\lambda }\] and \[f\left( f\left( x \right) \right)=x\] , then \[\lambda \] is equal to
(A) 2018
(B) 2019
(C) -2019
(D) -2018
Answer
477.6k+ views
Hint: First of all, find \[f\left( f\left( x \right) \right)\] by using the basic procedure that when \[x\] in \[f\left( x \right)\] is replaced by \[f\left( x \right)\] then, \[f\left( f\left( x \right) \right)\] is obtained. Since \[f\left( f\left( x \right) \right)\] is equal to \[x\] so, make the obtained \[f\left( f\left( x \right) \right)\] equal to \[x\] . Now, use the formula, \[\left( {{a}^{2}}-{{b}^{2}} \right)=\left( a+b \right)\left( a-b \right)\] and simplify it further. Finally, solve for \[\lambda \] .
Complete step by step answer:
According to the question, we are given a function \[f\left( x \right)\] , and the value of \[f\left( f\left( x \right) \right)\] is equal to \[x\] . Using all information, we are asked to find the value of the unknown term \[\lambda \] .
The given function is \[f\left( x \right)=\dfrac{2018x-2019}{x+\lambda }\] ……………………………………..(1)
Also, \[f\left( f\left( x \right) \right)=x\] …………………………………….(2)
In the above equation, we can observe that we require \[f\left( f\left( x \right) \right)\] .
We know the procedure to find \[f\left( f\left( x \right) \right)\] when \[f\left( x \right)\] is given i.e when \[x\] in \[f\left( x \right)\] is replaced by \[f\left( x \right)\] then, \[f\left( f\left( x \right) \right)\] is obtained.
Now, on replacing x by \[f\left( x \right)\] in equation (1), we get
\[f\left( f\left( x \right) \right)=\dfrac{2018f\left( x \right)-2019}{f\left( x \right)+\lambda }\] …………………………………(3)
Using equation (1) and on replacing \[f\left( x \right)\] by \[f\left( x \right)=\dfrac{2018x-2019}{x+\lambda }\] in equation (3), we get
\[\begin{align}
& \Rightarrow f\left( f\left( x \right) \right)=\dfrac{2018f\left( x \right)-2019}{f\left( x \right)+\lambda } \\
& \Rightarrow f\left( f\left( x \right) \right)=\dfrac{2018\left( \dfrac{2018x-2019}{x+\lambda } \right)-2019}{\left( \dfrac{2018x-2019}{x+\lambda } \right)+\lambda } \\
& \Rightarrow f\left( f\left( x \right) \right)=\dfrac{\dfrac{{{\left( 2018 \right)}^{2}}x-2018\times 2019-2019\left( x+\lambda \right)}{\left( x+\lambda \right)}}{\dfrac{\left( 2018x-2019 \right)+\lambda x+{{\lambda }^{2}}}{\left( x+\lambda \right)}} \\
\end{align}\]
\[\Rightarrow f\left( f\left( x \right) \right)=\dfrac{{{\left( 2018 \right)}^{2}}x-2018\times 2019-2019\left( x+\lambda \right)}{\left( 2018x-2019 \right)+\lambda x+{{\lambda }^{2}}}\] ………………………………………(4)
But, from equation (2), we have \[f\left( f\left( x \right) \right)=x\] .
Now, on replacing \[f\left( f\left( x \right) \right)\] by \[x\] in equation (4), we get
\[\begin{align}
& \Rightarrow x=\dfrac{{{\left( 2018 \right)}^{2}}x-2018\times 2019-2019\left( x+\lambda \right)}{\left( 2018x-2019 \right)+\lambda x+{{\lambda }^{2}}} \\
& \Rightarrow x\left\{ \left( 2018x-2019 \right)+\lambda x+{{\lambda }^{2}} \right\}={{\left( 2018 \right)}^{2}}x-2018\times 2019-2019\left( x+\lambda \right) \\
& \Rightarrow 2018{{x}^{2}}-2019x+\lambda {{x}^{2}}+{{\lambda }^{2}}x={{\left( 2018 \right)}^{2}}x-2018\times 2019-2019x-2019\lambda \\
& \Rightarrow \left( 2018+\lambda \right){{x}^{2}}+{{\lambda }^{2}}x={{\left( 2018 \right)}^{2}}x-2018\times 2019-2019\lambda \\
& \Rightarrow \left( 2018+\lambda \right){{x}^{2}}+x\left( {{\lambda }^{2}}-{{2018}^{2}} \right)+2018\times 2019+2019\lambda =0 \\
\end{align}\]
\[\Rightarrow \left( 2018+\lambda \right){{x}^{2}}+x\left( {{\lambda }^{2}}-{{2018}^{2}} \right)+2019\left( 2018+\lambda \right)=0\] ………………………………..(5)
We know the formula that \[\left( {{a}^{2}}-{{b}^{2}} \right)=\left( a+b \right)\left( a-b \right)\] …………………………………………..(6)
Now, from equation (5) and equation (6), we get
\[\Rightarrow \left( 2018+\lambda \right){{x}^{2}}+x\left( \lambda -2018 \right)\left( \lambda +2018 \right)+2019\left( 2018+\lambda \right)=0\] ………………………………………….(7)
In the above equation, we can observe that the term \[\left( \lambda +2018 \right)\] can be taken as common from the whole.
Now, on taking the term \[\left( \lambda +2018 \right)\] out as common from the whole, we get
\[\Rightarrow \left( 2018+\lambda \right)\left\{ {{x}^{2}}+x\left( \lambda -2018 \right)+2019 \right\}=0\]
So, either \[\left( 2018+\lambda \right)=0\] or \[\left\{ {{x}^{2}}+x\left( \lambda -2018 \right)+2019 \right\}=0\]
Here, we can ignore the term \[\left\{ {{x}^{2}}+x\left( \lambda -2018 \right)+2019 \right\}=0\] . Since we don’t know any restrictions on the value of x and we are asked to find the value of \[\lambda \] so, it is just too complex to find the value of \[\lambda \] using this equation.
Now, let us proceed with \[\left( 2018+\lambda \right)=0\] .
\[\begin{align}
& \Rightarrow \left( 2018+\lambda \right)=0 \\
& \Rightarrow \lambda =-2018 \\
\end{align}\]
Here, we have the value of \[\lambda \] .
Therefore, the value of \[\lambda \] is -2018.
So, the correct answer is “Option D”.
Note: Whenever this type of question appears where \[f\left( x \right)\] is given and there is a requirement of \[f\left( f\left( x \right) \right)\] . Use the basic procedure to find \[f\left( f\left( x \right) \right)\] i.e, to calculate \[f\left( f\left( x \right) \right)\] , just replace x by \[f\left( x \right)\] in the function of \[f\left( x \right)\] and calculate \[f\left( f\left( x \right) \right)\] .
Complete step by step answer:
According to the question, we are given a function \[f\left( x \right)\] , and the value of \[f\left( f\left( x \right) \right)\] is equal to \[x\] . Using all information, we are asked to find the value of the unknown term \[\lambda \] .
The given function is \[f\left( x \right)=\dfrac{2018x-2019}{x+\lambda }\] ……………………………………..(1)
Also, \[f\left( f\left( x \right) \right)=x\] …………………………………….(2)
In the above equation, we can observe that we require \[f\left( f\left( x \right) \right)\] .
We know the procedure to find \[f\left( f\left( x \right) \right)\] when \[f\left( x \right)\] is given i.e when \[x\] in \[f\left( x \right)\] is replaced by \[f\left( x \right)\] then, \[f\left( f\left( x \right) \right)\] is obtained.
Now, on replacing x by \[f\left( x \right)\] in equation (1), we get
\[f\left( f\left( x \right) \right)=\dfrac{2018f\left( x \right)-2019}{f\left( x \right)+\lambda }\] …………………………………(3)
Using equation (1) and on replacing \[f\left( x \right)\] by \[f\left( x \right)=\dfrac{2018x-2019}{x+\lambda }\] in equation (3), we get
\[\begin{align}
& \Rightarrow f\left( f\left( x \right) \right)=\dfrac{2018f\left( x \right)-2019}{f\left( x \right)+\lambda } \\
& \Rightarrow f\left( f\left( x \right) \right)=\dfrac{2018\left( \dfrac{2018x-2019}{x+\lambda } \right)-2019}{\left( \dfrac{2018x-2019}{x+\lambda } \right)+\lambda } \\
& \Rightarrow f\left( f\left( x \right) \right)=\dfrac{\dfrac{{{\left( 2018 \right)}^{2}}x-2018\times 2019-2019\left( x+\lambda \right)}{\left( x+\lambda \right)}}{\dfrac{\left( 2018x-2019 \right)+\lambda x+{{\lambda }^{2}}}{\left( x+\lambda \right)}} \\
\end{align}\]
\[\Rightarrow f\left( f\left( x \right) \right)=\dfrac{{{\left( 2018 \right)}^{2}}x-2018\times 2019-2019\left( x+\lambda \right)}{\left( 2018x-2019 \right)+\lambda x+{{\lambda }^{2}}}\] ………………………………………(4)
But, from equation (2), we have \[f\left( f\left( x \right) \right)=x\] .
Now, on replacing \[f\left( f\left( x \right) \right)\] by \[x\] in equation (4), we get
\[\begin{align}
& \Rightarrow x=\dfrac{{{\left( 2018 \right)}^{2}}x-2018\times 2019-2019\left( x+\lambda \right)}{\left( 2018x-2019 \right)+\lambda x+{{\lambda }^{2}}} \\
& \Rightarrow x\left\{ \left( 2018x-2019 \right)+\lambda x+{{\lambda }^{2}} \right\}={{\left( 2018 \right)}^{2}}x-2018\times 2019-2019\left( x+\lambda \right) \\
& \Rightarrow 2018{{x}^{2}}-2019x+\lambda {{x}^{2}}+{{\lambda }^{2}}x={{\left( 2018 \right)}^{2}}x-2018\times 2019-2019x-2019\lambda \\
& \Rightarrow \left( 2018+\lambda \right){{x}^{2}}+{{\lambda }^{2}}x={{\left( 2018 \right)}^{2}}x-2018\times 2019-2019\lambda \\
& \Rightarrow \left( 2018+\lambda \right){{x}^{2}}+x\left( {{\lambda }^{2}}-{{2018}^{2}} \right)+2018\times 2019+2019\lambda =0 \\
\end{align}\]
\[\Rightarrow \left( 2018+\lambda \right){{x}^{2}}+x\left( {{\lambda }^{2}}-{{2018}^{2}} \right)+2019\left( 2018+\lambda \right)=0\] ………………………………..(5)
We know the formula that \[\left( {{a}^{2}}-{{b}^{2}} \right)=\left( a+b \right)\left( a-b \right)\] …………………………………………..(6)
Now, from equation (5) and equation (6), we get
\[\Rightarrow \left( 2018+\lambda \right){{x}^{2}}+x\left( \lambda -2018 \right)\left( \lambda +2018 \right)+2019\left( 2018+\lambda \right)=0\] ………………………………………….(7)
In the above equation, we can observe that the term \[\left( \lambda +2018 \right)\] can be taken as common from the whole.
Now, on taking the term \[\left( \lambda +2018 \right)\] out as common from the whole, we get
\[\Rightarrow \left( 2018+\lambda \right)\left\{ {{x}^{2}}+x\left( \lambda -2018 \right)+2019 \right\}=0\]
So, either \[\left( 2018+\lambda \right)=0\] or \[\left\{ {{x}^{2}}+x\left( \lambda -2018 \right)+2019 \right\}=0\]
Here, we can ignore the term \[\left\{ {{x}^{2}}+x\left( \lambda -2018 \right)+2019 \right\}=0\] . Since we don’t know any restrictions on the value of x and we are asked to find the value of \[\lambda \] so, it is just too complex to find the value of \[\lambda \] using this equation.
Now, let us proceed with \[\left( 2018+\lambda \right)=0\] .
\[\begin{align}
& \Rightarrow \left( 2018+\lambda \right)=0 \\
& \Rightarrow \lambda =-2018 \\
\end{align}\]
Here, we have the value of \[\lambda \] .
Therefore, the value of \[\lambda \] is -2018.
So, the correct answer is “Option D”.
Note: Whenever this type of question appears where \[f\left( x \right)\] is given and there is a requirement of \[f\left( f\left( x \right) \right)\] . Use the basic procedure to find \[f\left( f\left( x \right) \right)\] i.e, to calculate \[f\left( f\left( x \right) \right)\] , just replace x by \[f\left( x \right)\] in the function of \[f\left( x \right)\] and calculate \[f\left( f\left( x \right) \right)\] .
Recently Updated Pages
Master Class 12 Social Science: Engaging Questions & Answers for Success

Class 12 Question and Answer - Your Ultimate Solutions Guide

Master Class 10 Computer Science: Engaging Questions & Answers for Success

Master Class 10 Maths: Engaging Questions & Answers for Success

Master Class 10 English: Engaging Questions & Answers for Success

Master Class 10 General Knowledge: Engaging Questions & Answers for Success

Trending doubts
The gas that burns in oxygen with a green flame is class 12 chemistry CBSE

Most of the Sinhalaspeaking people in Sri Lanka are class 12 social science CBSE

And such too is the grandeur of the dooms We have imagined class 12 english CBSE

What I want should not be confused with total inactivity class 12 english CBSE

Write a short note on Franklands reaction class 12 chemistry CBSE

Franz thinks Will they make them sing in German even class 12 english CBSE
